Academic Performance of College Students Awarded with Financial Aid: A Literature Review [Desempeño Académico de Estudiantes Universitarios Con Ayudas Financieras: Una Revisión de Literatura*] - Gallardo-Canales, R (Universidad del Zulia, 2021)
In recent years, a significant increase of limited resources students attending university has been observed, as a response to higher financial aid through scholarships and loans. Nevertheless, it is unclear their effectiveness considering the withholding rates, persistency, and graduation. The present study has taken as an objective to identify the effects of financial aid on student achievement indicators through a systematic international literature revision from 2015 to 2020 to establish relations between student performance and financial aid. Results demonstrate that, in the case of scholarships, the effect is positive within the ambits of performance and graduation; by comparison, loans’ effects are heterogeneous and show a financial stress for students. To conclude, the necessity of future investigations is clear in order to consistently determine loans’ significance related to academic results because of the large investment in this field, as well as the relation between students’ profile and academic institutions regarding the impact of funding programs; in order to contribute to the selection of effective programs and public policy decision-making. © 2021, Universidad del Zulia. All rights reserved.